2010
DOI: 10.1016/j.mcn.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human ES and Parkinson's disease iPS cells into ventral midbrain dopaminergic neurons requires a high activity form of SHH, FGF8a and specific regionalization by retinoic acid

Abstract: The cardinal motor symptoms of Parkinson's disease (PD) are caused by the vulnerability to dysfunction and degeneration of ventral midbrain (VM) dopaminergic (DA) neurons. A major limitation for experimental studies of current ES/iPS cell differentiation protocols is the lack of VM DA neurons with a stable phenotype as defined by an expression marker code of FOXA2/TH/β-tubulin. Here we demonstrate a combination of three modifications that were required to produce VM DA neurons. Firstly, early and specific expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 59 publications
7
159
0
1
Order By: Relevance
“…This report further characterized the MSC-DP cells and found that they were double positive for FOXA2 and GIRK2, both specific markers of differentiated A9 dopaminergic neurons. In particular, FOXA2 was recently identified as a transcription factor required for specifying and maintaining the dopaminergic neuron phenotype (28,42) and is considered to be expressed exclusively in floor plate-derived dopaminergic neurons (43). We confirmed the coexpression of FOXA2 and GIRK2 in SNc tissue that contains A9 dopaminergic neurons but not in the VTA, which contains A10 dopaminergic neurons.…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…This report further characterized the MSC-DP cells and found that they were double positive for FOXA2 and GIRK2, both specific markers of differentiated A9 dopaminergic neurons. In particular, FOXA2 was recently identified as a transcription factor required for specifying and maintaining the dopaminergic neuron phenotype (28,42) and is considered to be expressed exclusively in floor plate-derived dopaminergic neurons (43). We confirmed the coexpression of FOXA2 and GIRK2 in SNc tissue that contains A9 dopaminergic neurons but not in the VTA, which contains A10 dopaminergic neurons.…”
Section: Figuresupporting
confidence: 71%
“…We confirmed the coexpression of FOXA2 and GIRK2 in SNc tissue that contains A9 dopaminergic neurons but not in the VTA, which contains A10 dopaminergic neurons. GIRK2/FOXA2 double-positive cells have not been induced from other stem cell sources using existing protocols (44)(45)(46), except for one that manipulates both the sonic hedgehog and WNT signaling pathways (43,47). Recent studies of fetal tissue engrafting in patients with PD or PD model rats have shown that A9 dopaminergic neurons are determinants of successful functional recovery (16,48) and decreased dyskinesia (49) and that they are associated with well-organized synaptic connectivity (16).…”
Section: Figurementioning
confidence: 99%
“…Notably, hES cellderived DA neurons also have not yet been shown to coexpress TH and foxA2 after transplantation using different differentiation protocols, including ours (12)(13)(14)(15), indicating that new strategies toward phenotypic patterning of hES and hiPSs cells during in vitro differentiation have to be pursued. During the course of this study, however, we and others have developed protocols that generate foxA2 + floor plate cells from hES cells (28) or foxA2 + DA neurons from hES and PDiPS cells in vitro (29), which provide encouraging cell sources for future transplantation studies to further improve axonal outgrowth and behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the most promising results have been obtained using embryonic stem (ES) cells [52][53][54][55][56][57][58][59][60][61][62] or therapeutically cloned ES cells [63]. The examples shown (Fig.…”
Section: Can Stem Cell-derived Neurons Replace Fetal Grafts In Pd Patmentioning
confidence: 99%
“…4) are derived from mouse ES cells, using forced expression of the transcription factor Lmx1a, according to the protocol published by Friling et al [62] in 2009. Other types of stem cells, such as NSCs and progenitors from the embryonic ventral mesencephalon [64][65][66][67], adult NSCs from the subventricular zone [68], bone marrow stromal cells [69], and fibroblast-derived induced pluripotent stem (iPS) cells [61,[70][71][72] have also been used for this purpose. It has also been shown that human stem cell-derived DA neuroblasts, which will be required for patient application, can survive in animal models of PD and after maturation exert functional effects [54,58,66,69,71,72].…”
Section: Can Stem Cell-derived Neurons Replace Fetal Grafts In Pd Patmentioning
confidence: 99%